2010
DOI: 10.1348/135910709x480346
|View full text |Cite
|
Sign up to set email alerts
|

Mood volatility with rumination but neither attentional nor interpretation biases in chronic fatigue syndrome

Abstract: Rumination and distraction lead to greater mood volatility in CFS individuals than in controls, but not to attentional nor interpretation biases in the early automatic stages of information processing in CFS individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…The Stroop studies found little support for an interference effect of illness‐related stimuli in CFS populations. In contrast, findings from the visual‐probe studies indicated that for people with CFS, health‐threatening and illness‐related information engages (500 ms) and maintains (1,250 ms) their attention more than neutral information; an attentional bias effect was not found for 100 ms (Martin & Alexeeva, ), indicating that in a CFS population, attentional bias may occur at the elaboration phase of the information processing system, rather than at the initial orientation phase. Thus, cognitive biases in CFS may represent a specific cognitive strategy developed to avoid further injury and disability.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…The Stroop studies found little support for an interference effect of illness‐related stimuli in CFS populations. In contrast, findings from the visual‐probe studies indicated that for people with CFS, health‐threatening and illness‐related information engages (500 ms) and maintains (1,250 ms) their attention more than neutral information; an attentional bias effect was not found for 100 ms (Martin & Alexeeva, ), indicating that in a CFS population, attentional bias may occur at the elaboration phase of the information processing system, rather than at the initial orientation phase. Thus, cognitive biases in CFS may represent a specific cognitive strategy developed to avoid further injury and disability.…”
Section: Discussionmentioning
confidence: 93%
“…Before the exogenous cueing task, all participants were randomly allocated to either a rumination induction (instructed to read/think about present physical sensations, emotions, and thoughts) or distraction induction (instructed to read/think about neutral external matters, such as objects). Martin and Alexeeva () found no support for an early attentional bias towards either illness‐related or social anxiety words in a CFS sample compared to healthy controls, even when participants were induced into a ruminative state.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These effects may be attributable to increased avoidance of health-threat rather than engagement with it (De Ruiter and Brosschot, 1994), however, or stimulus negativity more generally (Posserud et al, 2009). Studies using the dot-probe and exogenous cueing paradigms have not found evidence of attentional bias in MUS patients (Chapman and Martin, 2011;Hou et al, 2008;Martin and Alexeeva, 2010;Martin and Chapman, 2010;van der Veek et al, 2014;Witthöft et al, 2006).…”
Section: Interoceptive Hypervigilance Thresholds and Awarenessmentioning
confidence: 96%